The phenomenon of Oleg Spivakov — taxidermist, artist, and museologist - Hrininh-Hera, K.; Zagorodniuk, I. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2026)
Oleg Spivakov is one of the most notable Ukrainian taxidermists of the late 20th and early 21st centuries, an artist, and a museum professional. Based on biographical data and an analysis of museum collections, this text highlights the formation of his unique signature style, which combines scientific accuracy with high artistic craftsmanship. A graduate of Taurida University, Oleg dedicated his life to the development of natural history museums: first, to the restoration the Museum of Nature and History of Karadag at the Karadag biostation (1982–2008), and later, to Zoological Museum of Taras Shevchenko National University in Kyiv (2009–2021). The master was virtuoso in the techniques of creating taxidermy sculptures across diverse taxonomic groups—from fish and amphibians to birds and mammals—and his works now grace countless state and private collections. The "Crimean period" of Oleg Spivakov’s career is analysed in detail, the key achievement of which was the revival of the Museum of Nature and History of Karadag. (In fact, it was a creation "from scratch," as no exhibits from the old collection remained). The article describes his innovative approach to building the exhibition according to the biotopic principle, where the author created over 400 specimens covering about 200 species of vertebrates. Furthermore, Oleg Spivakov made a significant contribution to the study of the Crimean fauna, particularly through the records of rare bird and mammal species that have entered scientific circulation. Special attention is paid to the ‘Kyiv period’, marked by the creation of taxidermy sculptures of fish, amphibians, and mammals. His role in the restoration of old collection specimens in the exhibition of the Zoological Museum of Kyiv University (ZMKU) is also characterised. Oleg Spivakov’s creative heritage in taxidermy represents a significant contribution to national museology, particularly in the formation and restoration of zoological exhibitions. His legacy is not limited to museum halls: the master’s works constitute a significant part of numerous private collections, where they are valued as unique pieces of art. The master’s works are distinguished by an exceptionally high artistic level, which effectively grants them the status of works of art.